Investigation of the Microstructure and Properties of TRIP 800 Steel Subjected to Low-Cycle Fatigues - Z. M. Rykavets, J. Bouquerel, J.-B. Vogt, Z. A. Duriagina, V. V. Kulyk, T. L. Tepla, L. I. Bohun, T. M. Kovbasyuk (Успехи физики металлов, 2019)
Low-alloyed TRIP steels are well known since the beginning of the 21st century and used for automotive applications to ensure the passive safety. However, although their behaviour is fully investigated at a monotonous behaviour, the case of cyclic loading is not well studied. The present work describes in detail the heterogeneous-microstructure evolution of a high-strength steel (TRIP 800 steel) at the low-cycle fatigue conditions. Based on the extended investigations (via the optical and electron microscopy, the electron backscattering diffraction), we propose suggestions on the influence of phase composition on the mechanical properties and the crack-initiation processes. The preferential places of the crack nucleation caused by fatigue are detected, and the completeness of phase transformation via the induced plasticity is evaluated.